2022
DOI: 10.3390/ijerph19159417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Real-Time Active Noise Control Devices in Dental Treatment Conditions

Abstract: Dental clinics are exposed to various uncomfortable noises. The aim of this study was to quantify the effectiveness of active noise control devices in dental treatment conditions. Two types of commercial headsets (Airpods Pro, QC30) and two types of dental headsets (Alltalk, Quieton Dental) were used for the experiment. Three sounds (high-speed handpiece, low-speed handpiece, and suction system) were measured at three different distances from the dental teeth model, typodont. The distances of 10, 40, and 70 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…However, from the experiment results and what is claimed on the QuietOn website, speech frequencies with this range were significantly suppressed. Based on this, the authors are in agreement with Kim et al 17 that while QuietOn can reduce some dental surgery background noise it would not meet the requirements of suppressing drill noise while also enabling verbal communication from dentist and dental nurse to the patient.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, from the experiment results and what is claimed on the QuietOn website, speech frequencies with this range were significantly suppressed. Based on this, the authors are in agreement with Kim et al 17 that while QuietOn can reduce some dental surgery background noise it would not meet the requirements of suppressing drill noise while also enabling verbal communication from dentist and dental nurse to the patient.…”
Section: Discussionsupporting
confidence: 75%
“…The results shown in this study plus four commercially-available ANC devices tested in a recent study by Kim et al, 17 found that the QuietOn device had the better characteristics overall. However, there is still a clear need for a device that is able to target dental handpiece noise and reduce the anxiety-inducing effect of dental drill noise for patients, while maintaining verbal communication.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We are looking to perform broader studies in this area of pediatric dentistry, as we can see that it is not only an important part of children's dental treatment but also a great area for the development of the VR industry. We also believe that noise reduction devices and computerized anesthesia instruments could make VR goggles more effective in order to help children undergoing dental procedures [40,41].…”
mentioning
confidence: 99%